Preferences and Behaviour of Tourists in Terms of Choice and Frequency of Trips: Qualitative and Quantitative Study in Poland - Anna S. KOWALSKA; Anna OLSZANSKA; Klaudia PASKUDZKA; Dominika KOWALSKA (Communications of International Proceedings, 2025)
The study aimed to identify and analyze the key determinants influencing consumer decisions in choosing accommodation services. Understanding these factors is essential for businesses in the tourism sector to effectively tailor their services to meet diverse customer expectations. Although various studies have explored consumer behavior in tourism, there remains a gap in understanding how specific socio-demographic variables interact with accommodation choices. This research addresses that gap by analyzing how factors such as age, gender, and financial situation influence preferences in accommodation type, destination, and travel patterns. A non-random, quota-targeted sampling method was used to collect data in October 2022. To assess statistically significant relationships between variables, Pearson’s χ² test, Cramer’s V, Yule’s φ, and Sommers’ dBA were applied. Additionally, a multivariate Profit analysis was conducted to strengthen the findings. The study found that accommodation choices are significantly influenced by socio-demographic characteristics. Age correlated with the length and frequency of trips, with older individuals preferring longer but fewer trips. Gender influenced destination choices — women favored seaside locations, while men leaned towards mountains. Financial status played a key role in accommodation selection, with higher-income individuals preferring hotels and apartments, and lower-income respondents opting for hostels and campsites. These insights underline the importance of targeted marketing strategies in the tourism industry.
Keywords: accommodation services; tourist trips; service quality; nonparametric tests